A Review of Nutrition-Sensitive Interventions in Bangladesh's Agri-Food Systems - Rasheed, Sabrina (WorldFish, 2024)
This study critically reviews nutrition-sensitive interventions within Bangladesh’s agri-food system, evaluating their status, effectiveness, and the socio-economic, cultural, and environmental factors influencing their success. It identifies key interventions for potential scaling and examines the alignment of national policies and international frameworks addressing nutrition and agriculture. This review is especially important considering the persistent high rates of undernutrition in Bangladesh, especially among women and children. By reviewing and understanding the current nutrition-sensitive interventions within the agri-food system in Bangladesh, the study aims to improve household and individual nutrition outcomes and inform evidence-based national policy improvements.